Some convergence theorems for order-Mcshane equi-integral in Riesz space - Shkembi, Mimoza; Temaj, Ismet (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper we prove some convergence theorems of order-Macshane equi -integrals on Banach lattice and arrive same result in L-space as on Mcshane norm-integrals.